2019
DOI: 10.1590/0004-282x20190087
|View full text |Cite
|
Sign up to set email alerts
|

Can the positions of the spastic upper limb in stroke survivors help muscle choice for botulinum toxin injections?

Abstract: Motor impairments in stroke survivors are prevalent and contribute to dependence in daily activities, pain and overall disability, which can further upper-limb disability. Treatment with botulinum toxin A (BoNT-A) is indicated for focal spasticity and requires knowledge of biomechanics and anatomy to best select muscles to be injected in the limb. Objective: We aimed to describe the frequency of posture patterns in a Brazilian sample of stroke survivors and correlate them with recommendations of muscle select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 16 publications
1
9
0
3
Order By: Relevance
“…The use of BoNT-A in the reduction of pain and improvement of ROM in the shoulder has been shown in a number of previous studies [24][25][26], with results from a meta-analysis of randomized controlled trials also reporting that BoNT injections showed more persistent clinical benefits in pain reduction and ROM compared with placebo or steroid injections [27]. The majority (82.8%) of patients in the current study presented with an adducted internally rotated shoulder; Gomes et al (2019) reported similar results in Brazilian patients with post-stroke motor impairment, with 76% of patients presenting with this pattern of UL spasticity [28]. Improving ROM, motor function, and mobility, and reducing pain are all common goals during rehabilitation post-stroke [29].…”
Section: Discussionsupporting
confidence: 64%
“…The use of BoNT-A in the reduction of pain and improvement of ROM in the shoulder has been shown in a number of previous studies [24][25][26], with results from a meta-analysis of randomized controlled trials also reporting that BoNT injections showed more persistent clinical benefits in pain reduction and ROM compared with placebo or steroid injections [27]. The majority (82.8%) of patients in the current study presented with an adducted internally rotated shoulder; Gomes et al (2019) reported similar results in Brazilian patients with post-stroke motor impairment, with 76% of patients presenting with this pattern of UL spasticity [28]. Improving ROM, motor function, and mobility, and reducing pain are all common goals during rehabilitation post-stroke [29].…”
Section: Discussionsupporting
confidence: 64%
“…Si bien existen estudios recientes que analizan la utilidad y distribución de frecuencias de los patrones de Hefter, la evidencia es limitada respecto al análisis específico de los patrones de muñeca y dedo, restringiendo así el análisis integral de la extremidad superior 9 .…”
Section: Discussionunclassified
“…La evaluación incluyó una observación clínica estandarizada, identificando: datos demográficos y clínicos, mas la pesquisa de patrones de EES, referidos a Hefter, muñeca, dedos y pulgar, los que se observaron en posición sedente y, cuando fue posible, en bipedestación sin asistencia o con ayuda de un bastón. Esta metodología ya fue empleada por investigadores anteriores 6,9 pero, a diferencia de ellos, este estudio utilizó la observación directa, a fin de hacer más objetiva la evaluación. No se adicionaron registros de video ni tampoco pruebas dinámicas (deambulación con o sin ayuda para la marcha) con el propósito de obtener el patrón natural de la extremidad superior, sin generar patrones sincinéticos que pudieran cambiar la posición del segmento evaluado ante los esfuerzos, fenómeno común en el SMNS 10 , y que ha sido reportado como un elemento que dificulta la clasificación de patrones 9 .…”
Section: Procedimientounclassified
See 1 more Smart Citation
“…For example, patients may be using slings to prevent capsular distension and reduce pain, which over time can result in deltoid muscle atrophy and affect posture independently of the spastic muscles. Furthermore, UL position can vary for rest/sitting vs. walking, potentially altering the observed spasticity pattern ( 36 ). Table 2 shows which muscles are typically affected for commonly reported impaired activities.…”
Section: Methodsmentioning
confidence: 99%